Politeness in professional contexts - Archer, Dawn; Grainger, Karen; Jagodzinski, Piotr (Pragmatics & beyond ;, 2020)
"Much like in everyday life, politeness is key to the smooth running of relationships and interactions. Professional contexts, however, tend to be characterised by a plethora of behaviours that may be specific to that context. They include 'polite' behaviours, 'impolite' behaviours and behaviours that arguably fall somewhere between - or outside - such concepts. The twelve chapters making up this edited collection explore these behaviours in a range of communication contexts representative of business, medical, legal and security settings. Between them, the contributions will help readers to theorize about - and in some cases operationalize (im)politeness and related behaviours for - these real-world settings. The authors take a broad, yet theoretically underpinned, definition of politeness and use it to help explain, analyse and inform professional interactions. They demonstrate the importance of understanding how interactions are negotiated and managed in professional settings. The edited collection has something to offer, therefore, to academics, professionals and practitioners alike"--